Developing an Organic Liquid Fertilizer Booklet to Support The Sustainable Reserve Food Garden (SRFG) Program at Tunggak Cerme, Wonomerto, Probolinggo - Novi Wulandari; Mimien Henie Irawati; Nugrahaningsih Nugrahaningsih (Universitas Tidar, 2018)
The aim of this study is to develop and test organic liquid fertilizer booklet to support SRFG program. This study used ADDIE model which consists of analyze, design, develop, implement, and evaluation. The product tests are validity test and practicality test. The validity test result by the material expert, media expert, and field practitioner are 95,5%, 98,5%, 97,9%, showed that the booklet is valid. The practicality test result is 91,1%, showed that the booklet is practical.